System and mathematical modeling of quadrotor dynamics - Goodman JM; Kim J; Gadsden SA; Wilkerson SA (SPIE, the international society for optics and photonics, 2015)
Unmanned aerial systems (UAS) are becoming increasingly visible in our daily lives; and range in operation from search and rescue, monitoring hazardous environments, and to the delivery of goods. One of the most popular UAS are based on a quad-rotor design. These are typically small devices that rely on four propellers for lift and movement. Quad-rotors are inherently unstable, and rely on advanced control methodologies to keep them operating safely and behaving in a predictable and desirable manner. The control of these devices can be enhanced and improved by making use of an accurate dynamic model. In this paper, we examine a simple quadrotor model, and note some of the additional dynamic considerations that were left out. We then compare simulation results of the simple model with that of another comprehensive model.
Keywords: 40 Engineering; 4006 Communications Engineering; 4009 Electronics, Sensors and Digital Hardware; 51 Physical Sciences; 5102 Atomic, Molecular and Optical Physics